How can I show that if a function $f$ from an open interval of the real numbers to an euclidean space is differentiable at a point $x_0$ in its domain, that is, the limit $\lim_{\epsilon \to 0;\ \epsilon \neq 0}\frac{f(x_0 + \epsilon) - f(x_0)}{\epsilon}$ exists, then the limit $$ \lim_{\substack{(x_2, x_1)\to (x_0,x_0);\\ x_1 \leq x_0 \leq x_2;\ x_1 \neq x_2}} \frac{f(x_2)-f(x_1)}{x_2 - x_1} $$ exists and is equal to the derivative of $f$ at $x_0$.

  • $\begingroup$ I struggle to understand the second limit process. Is that a 2D limit $(x_1, x_2) \to (x_0, x_0)$? $\endgroup$ – mvw Aug 16 '18 at 19:25
  • $\begingroup$ Hint: Set $x_1=x_0$ and set $x_2=x_1+\epsilon$. $\endgroup$ – The Count Aug 16 '18 at 19:42
  • $\begingroup$ @TheCount Yes, that shows that the limits are equal if the desired limit exists, but it does not show that the desired limit exists. $\endgroup$ – user109871 Aug 16 '18 at 19:43
  • $\begingroup$ Differentiability is more or less equivalent to the first limit you have written, but I see what you mean. $\endgroup$ – The Count Aug 16 '18 at 19:46

This is actually rather straightforward. Assume (temporarily) that $x_1 < x_0 < x_2$. Under your assumptions at least one of these inequalities must be strict. Observe $$\frac{f(x_2) - f(x_1)}{x_2 - x_1} = \frac{f(x_2) - f(x_0)}{x_2 - x_0} \cdot \frac{x_2 - x_0}{x_2 - x_1} + \frac{f(x_1) - f(x_0)}{x_1 - x_0} \cdot \frac{x_0 - x_1}{x_2 - x_1}$$ and $$ f'(x_0) = f'(x_0) \cdot \frac{x_2 - x_0}{x_2 - x_1} + f'(x_0) \cdot \frac{x_0 - x_1}{x_2 - x_1}.$$ It follows that $\displaystyle \left| \frac{f(x_2) - f(x_1)}{x_2 - x_1} - f'(x_0) \right|$ is bounded by $$ \left| \frac{f(x_2) - f(x_0)}{x_2 - x_0} - f'(x_0) \right| \cdot \frac{x_2 - x_0}{x_2 - x_1} + \left| \frac{f(x_1) - f(x_0)}{x_0 - x_1} - f'(x_0) \right|\cdot \frac{x_0 - x_1}{x_2 - x_1}.$$ Absolute values are not required on the fractions since the terms are positive.

In the general case, if either $x_2 = x_0$ or $x_1 = x_0$ just omit the offending term; the remaining term provides the upper bound.

Now it just needs quantifiers: fix $\epsilon > 0$ and choose $\delta > 0$ so that $0 < |x - x_0| < \delta$ implies $$ \left| \frac{f(x) - f(x_0)}{x - x_0} - f'(x_0) \right| < \epsilon.$$

Then $|x_2 - x_1| < \delta$ along with the condition $x_1 \le x_0 \le x_2$ implies simultaneously that $|x_1 - x_0| < \delta$ and $|x_2 - x_0| < \delta$, so that $$\left| \frac{f(x_2) - f(x_1)}{x_2 - x_1} - f'(x_0) \right| < \epsilon \cdot \frac{x_2 - x_0}{x_2 - x_1} + \epsilon \cdot \frac{x_0 - x_1}{x_2 - x_1} = \epsilon.$$


Assume $x_0=0$ and $f'(0)=a$. Then one has $$f(x)=f(0)+ ax + x r(x)$$ whereby $$\lim_{x\to0} r(x)=r(0)=0\ .\tag{1}$$ It follows that $$f(x_2)-f(x_1)=a(x_2-x_1)+x_2 r(x_2)-x_1 r(x_1)$$ and therefore $${f(x_2)-f(x_1)\over x_2-x_1}-a={x_2\over x_2-x_1}r(x_2)-{x_1\over x_2-x_1}r(x_1)\qquad(x_1<x_2)\ .$$ If $x_1\leq0\leq x_2$ we therefore have $$\left|{f(x_2)-f(x_1)\over x_2-x_1}-a\right|\leq \bigl|r(x_2)\bigr|+\bigl|r(x_1)\bigr|\qquad(x_1<x_2)\ ,$$ so that the claim follows from $(1)$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.